2018
DOI: 10.1111/raq.12280
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessments of aquaculture systems: a critical review of reported findings with recommendations for policy and system development

Abstract: The aquaculture sector is anticipated to be a keystone in food production systems in the coming decades. However, it is associated with potentially important environmental damages caused by its contribution to eutrophication or climate change, for example. To comprehensively quantify those impacts, life cycle assessment (LCA) studies have been conducted on several seafood farming systems for the past 15 years. But, what major findings and common trends can we draw from this pool of studies? What can we learn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 83 publications
0
82
0
Order By: Relevance
“…Aquaculture has occasionally been thought to be associated with multiple potential environmental impacts such as eutrophication of aquatic ecosystems, ecotoxicity in local ecosystems, climate change and coastal acidification (Clements & Chopin 2017; Bohnes et al . 2018). A recent LCA study showed that culture type has little influence on the environmental impacts except for aquatic eutrophication, and IMTA may have the potential to decrease environmental impacts if the different species are wisely selected and combines (Bohnes et al .…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…Aquaculture has occasionally been thought to be associated with multiple potential environmental impacts such as eutrophication of aquatic ecosystems, ecotoxicity in local ecosystems, climate change and coastal acidification (Clements & Chopin 2017; Bohnes et al . 2018). A recent LCA study showed that culture type has little influence on the environmental impacts except for aquatic eutrophication, and IMTA may have the potential to decrease environmental impacts if the different species are wisely selected and combines (Bohnes et al .…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…A recent LCA study showed that culture type has little influence on the environmental impacts except for aquatic eutrophication, and IMTA may have the potential to decrease environmental impacts if the different species are wisely selected and combines (Bohnes et al . 2018). Another recent study has concluded that when not accounting for uncertainties (deterministic LCA results), IMTA was the best performing option for all impacts considered in their LCA comparison with monocultures (Beltran et al .…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…Following the accumulation of aquaculture LCA studies, several reviews recently analyzed this section of the literature, focusing on the application of the LCA methodology [37][38][39] and comparing production systems [40][41][42][43]. In the latter ones, attempts to compare results focused primarily on the comparison of the system's intensities (intensive, semi-intensive, and extensive) and culture types (polyculture vs. monoculture).…”
Section: Introductionmentioning
confidence: 99%
“…In fish cage production, the amount of feed provided to produce a unit of biomass (FCR) varies between species and among the different aquaculture systems used [8,14]. Even within one species and system, it may vary from fish farm to fish farm, which is why, when a sensitivity analysis is carried out [1], it is usually applied in relation to this system component, with one or two alternative scenarios proposed [8,11,15].…”
Section: Introductionmentioning
confidence: 99%